SOCIO-ECONOMIC AND CULTURAL ISSUES FACED BY DISABLED POPULATION: A CASE STUDY OF CHAKWAL CITY - Dr. Sadia Jabeen; Dr. Sonia Omer; Ms. Nimra Ikhlaq (International Journal of Contemporary Issues in Social Sciences, 2024)
Disability is the outcome of an impairment, which can be physical, cognitive, intellectual, sensory, developmental, or a combination of these, that limits an individual's capacity to participate in usual social activities. People with disabilities make up a large proportion of Pakistan's population. This greater minority is subject to discrimination in social life. Different governmental and private sector projects are being designed for people with disabilities. However, there is an urgent obligation to speak on the issues experienced by people with impairments. The study focuses on the socio-economic, cultural and behavioral challenges faced by marginalized population in Chakwal, Pakistan. The study is qualitative in nature. By using purposive sampling method, in-depth interviews have been conducted with disabled persons. Thematic analysis was used to analyze the data. The findings demonstrate that people with disabilities face severe socioeconomic and cultural barriers. They also confront behavioral challenges from society, as well as disability-related discrimination. Children with disabilities experience troubles in school, and their parents also confront issues as their children attend school. Owing to their disability and attitudinal problems from society, very few of them complete their education, and most of them drop out in the early levels of education. The study concluded that marginalized populations face socio-economic and cultural discrimination in our society. There is a need to give importance and keen attention towards this issue at the governmental level and by the general public.